Literatur Review Manajemen Energi Listrik dan Audit Energi pada Gedung - Rifqi Wibowo (Indo Publishing, 2026)
The increase in electricity consumption in buildings in Indonesia is often not accompanied by optimal energy efficiency, thus burdening operational costs and national energy security. This literature review aims to analyze energy management and audit strategies in various building categories, ranging from government offices and shopping centers to educational facilities. This research design includes a literature review, which involves identifying and analyzing theories. The method used is a comparative analysis of energy audit results based on the SNI 6196:2011 standard and government regulations related to Energy Consumption Intensity (IKE). The results of this literature review are related to electrical energy management and energy audits in buildings. There are no gaps in this research. The literature review is supported by 13 national journals.